Urban Readings on Public Art Representations in Landscape Architecture - Aysel Yavuz; Habibe Acar; Nihan Canbakal Ataoğlu (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Being a social presence, people participate in social life in the public spaces of the city. In these areas, they are in perceptual and physical contact with each other and get the opportunity to socialize. Social life culture contributes to urban culture and urban identity while keeping communities together. Cities creates areas for people to express themselves outside of their basic needs. The art used in the expression of an emotion, design and beauty has been included in our socio-cultural life in public spaces over time. Public art, which provides social, physical, environmental and economic contributions to the society and the city, is a manifestation of a multi-layered and multi-dimensional expression that includes different representations. Public art representations are important urban images and are the sensory components of collective memory. Today, in the process where the cities start to look alike, public art representations identified with the place make sense of the space and contribute to the identity of the city. In our study, the approach of landscape architecture to this subject will be evaluated by making important public art representations and city readings.